The impact of ESG implementation and green innovation on the financial performance of companies listed on the IDX ESG leaders index (2020-2022) - Ramadhana, Luqman Arief; Effendi, Syahrul (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2024)
This study aims to examine the impact of Environmental, Social, and Governance (ESG) performance and green innovation on the financial performance of companies. Economic performance is measured using Tobin's Q, while ESG and green innovation are measured using indicators established by the researchers. The research population comprises all 30 companies listed on the IDX ESG Leaders Index between 2020 and 2022. Applying purposive sampling criteria, a final sample of 19 companies was selected for analysis. The findings reveal a contrasting influence of the two independent variables. The ESG performance variable demonstrates a negative and significant effect on corporate financial performance. Conversely, green innovation exhibits a positive and significant impact. Furthermore, the control variables, company size and leverage, are also proven to influence financial performance significantly. These findings indicate that while green innovation directly contributes to enhanced financial outcomes, the current implementation of ESG practices may incur short-term costs that outweigh its immediate economic benefits. Article Information:Received 10/2/2024 / Revised 11/22/2024 / Accepted 12/6/2024 / Online First 12/22/2024